A novel compliance-pressure loop approach to quantify arterial compliance in systole and in diastole. (1st August 2018) - Kaya, Mehmet; Balasubramanian, Vignesh; Patel, Amit; Ge, Yueya; Li, John K-J.
Abstract: Arterial compliance has been recognized as a critical parameter in governing pulsatile flow dynamics. It has traditionally been assumed constant throughout the cardiac cycle and its computation has been based either on the classic Windkessel model (C) in diastole or the stroke volume over pulse pressure (Cv ) method in systole. Other methods using area (Cam ) or two-area (Ctam ) and exponential (C(P)exp1 ) methods were used for the cardiac cycle. We proposed a novel compliance-pressure loop (CPP loop) approach for the quantification of arterial compliance and compared it to existing linear and nonlinear methods. Experimental data were gathered in 5 dogs and blood pressure levels were varied (systolic pressure of 100 mmHg–185 mmHg) with induced hypertension and vasodilation. Results showed the limited regime of validity of C (Control:0.4681 ± 0.1270 ml/mmHg, MTX:0.3015 ± 0.1264 ml/mmHg and NTP:1.8323 ± 0.7207 ml/mmHg) and Cv (Control:0.3583 ± 0.0158 ml/mmHg, MTX:0.2602 ± 0.1275 ml/mmHg and NTP:0.4131 ± 0.0589 ml/mmHg), Cam (Control:0.4175 ± 0.0505, MTX:0.3086 ± 0.1568 and NTP:1.4181 ± 0.4812) and Ctam (Control: 0.2064 ± 0.0228 ml/mmHg, MTX:0.1967 ± 0.0884 ml/mmHg, NTP:0.0881 ± 0.0375 ml/mmHg) and that C(P)exp1 underestimates the arterial compliance compared to our method (Control:0.2233 ± 0.0168 ml/mmHg vs 0.4481 ± 0.0515 ml/mmHg, MTX:0.1976 ± 0.0964 ml/mmHg vs 0.3273 ± 0.1443 ml/mmHg and NTP: 0.2177 ± 0.0273 ml/mmHg vs 1.9990 ± 1.8221 ml/mmHg at mean arterial pressure). The CPP method based on the exponential method is superior, as it provides continuous compliance variations and CPP loop area can be readily visualized from hypotension to hypertension conditions. We conclude that the concept of using compliance-pressure loop is advantageous as it can afford continuous and accurate tracking of the dynamic arterial behavior despite greatly varying blood pressure levels. Highlights: A non-linear model of the arterial compliance is developed using Windkessel model. Model takes into account the stiffening property of arteries. Compliance varies over a complete cardiac cycle with aortic pressure. Model can be used to assess efficacy of hypertensive drugs. Compliance-Pressure loops afford continuous dynamic tracking of the arterial system.